THE IMPORTANCE OF INDIVIDUAL VARIATION IN DEFINING HABITAT SELECTION BY MOOSE IN NORTHERN BRITISH COLUMBIA - Gillingham, Michael P; Parker, Katherine L (Lakehead University, 2008)
Understanding resource use and selection has been central to many studies of ungulate ecology. Global positioning satellite (GPS) collars, remote sensing, and geographic information systems (GIS) now make it easier to examine variation in use and selection by individuals. Resource selection functions, however, are commonly developed for global (all animals pooled) models and important information on individual variability may be lost. Using data from 14 female moose (Alces alces) collared in the Muskwa-Kechika Management Area of northern British Columbia, we examined differences among global and individual resource selection models for 5 seasons (winter, late winter, calving, summer, and fall). The global models indicated that moose selected for mid-elevations, and for deciduous burns and Carex sedge areas in all seasons. Resource selection models for individuals, however, indicated that no individuals selected the same attributes as the global models. We also examined selection ratios among seasons with individual moose as replicates, and within individuals with bootstrapping techniques. We discuss the importance of considering individual variation in defining resource selection and habitat use by moose and contrast the results of selection ratios and resource selection models. We also use these data to illustrate some of the pitfalls that can be encountered using the 2 methodologies.